Exercise restriction is not associated with increasing body mass index over time in patients with anomalous aortic origin of the coronary arteries. (2nd May 2017) - Meza, James M.; Elias, Matthew D.; Wilder, Travis J.; O'Brien, James E.; Kim, Richard W.; Mavroudis, Constantine; Williams, William G.; Brothers, Julie; Cohen, Meryl S.; McCrindle, Brian W.
Abstract: Anomalous aortic origin of the coronary arteries is associated with exercise-induced ischaemia, leading some physicians to restrict exercise in patients with this condition. We sought to determine whether exercise restriction was associated with increasing body mass index over time. From 1998 to 2015, 440 patients ⩽30 years old were enrolled into an inception cohort. Exercise-restriction status was documented in 143 patients. Using linear mixed model repeated-measures regression, factors associated with increasing body mass index z-score over time, including exercise restriction and surgical intervention as time-varying covariates, were investigated. The 143 patients attended 558 clinic visits for which exercise-restriction status was recorded. The mean number of clinic visits per patient was 4, and the median duration of follow-up was 1.7 years (interquartile range (IQR) 0.5–4.4). The median age at first clinic visit was 10.3 years (IQR 7.1–13.9), and 71% (101/143) were males. All patients were alive at their most recent follow-up. At the first clinic visit, 54% (78/143) were exercise restricted, and restriction status changed in 34% (48/143) during follow-up. The median baseline body mass index z-score was 0.2 (IQR 0.3–0.9). In repeated-measures analysis, neither time-related exercise restriction nor its interaction with time was associated with increasing body mass index z-score. Surgical intervention and its interaction with time were associated with decreasing body mass index z-score. Although exercise restriction was not associated with increasing body mass index over time, surgical intervention was associated with decreasing body mass index z-score over time in patients with anomalous aortic origin of the coronary arteries.